Low-Intensity Focused Ultrasound Alleviates Spasticity and Increases Expression of the Neuronal K-Cl Cotransporter in the L4–L5 Sections of Rats Following Spinal Cord Injury - Liao, Ye-Hui; Chen, Mo-Xian; Chen, Shao-Chun; Luo, Kai-Xuan; Wang, Bing; Ao, Li-Juan; Liu, Yao (Frontiers in Cellular Neuroscience, 2022)
Low-intensity focused ultrasound (LIFU) has been shown to provide effective activation of the spinal cord neurocircuits. The aim of this study was to investigate the effects of LIFU in order to alleviate spasticity following spinal cord injury (SCI) by activating the spinal neurocircuits and increasing the expression of the neuronal K-Cl cotransporter KCC2. Adult male Sprague Dawley (SD) rats (220–300 g) were randomly divided into a sham control group, a LIFU− group, and a LIFU+ group. The mechanical threshold hold (g) was used to evaluate the behavioral characteristics of spasm. Electromyography (EMG) was used to assess activation of the spinal cord neurocircuits and muscle spontaneous contraction. Spasticity was assessed by frequency-dependent depression (FDD). The expression of KCC2 of the lumbar spinal cord was determined via western blot (WB) and immunofluorescence (IF) staining. The spinal cord neurocircuits were activated by LIFU simulation, which significantly reduced the mechanical threshold (g), FDD, and EMG recordings (s) after four weeks of treatment. WB and IF staining both demonstrated that the expression of KCC2 was reduced in the LIFU− group (P < 0.05). After four weeks of LIFU stimulation, expression of KCC2 had significantly increased (P < 0.05) in the LIFU+ group compared with the LIFU− group. Thus, we hypothesized that LIFU treatment can alleviate spasticity effectively and upregulate the expression of KCC2 in the L4–L5 section of SCI rats.